2019
DOI: 10.1101/702076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of intracellular and extracellular antibiotic resistance gene abundance in anaerobic membrane bioreactor effluent

Abstract: The growing practice of wastewater reuse poses a significant risk to further 13 dissemination of antibiotic resistance due to the abundance of antibiotic resistance 14 bacteria (ARB) and antibiotic resistance genes (ARGs) in wastewater effluents. Anaerobic 15 membrane bioreactors (AnMBRs) are an emerging wastewater treatment technology 16 capable of reducing the total ARGs and ARB load discharged to receiving environments 17 compared to conventional aerobic treatment processes. While size exclusion is effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Other sulfa-ARGs showed a lower abundance in the R 1 effluent, while sul1 and sul2 were highly expressed in R 2 (Figure S9), consistent with Zhang et al’s report, in which long-term removal of SMX in the BGS system fostered the enrichment of sul1 and sul2 . Various-sized plasmids can act as carriers of these genes . Different trends were observed for other subtypes, with overall concentrations being significantly lower ( p < 0.05) in R 1 compared to R 2 (Figures S9–S12).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Other sulfa-ARGs showed a lower abundance in the R 1 effluent, while sul1 and sul2 were highly expressed in R 2 (Figure S9), consistent with Zhang et al’s report, in which long-term removal of SMX in the BGS system fostered the enrichment of sul1 and sul2 . Various-sized plasmids can act as carriers of these genes . Different trends were observed for other subtypes, with overall concentrations being significantly lower ( p < 0.05) in R 1 compared to R 2 (Figures S9–S12).…”
Section: Resultssupporting
confidence: 88%
“…Calero-Cáceres et al noted a transition in ARG prevalence during secondary treatment, with specific ARG types becoming more pronounced in sludge samples . Wang et al observed a striking effluent–biomass exchange of ARGs in the sludge reactor, which was plasmid-mediated . Here, the transposons and plasmids, representing >75% of the total MGEs (Figure S5), showed biomass preference at low antibiotic spiking, suggesting the biomass as an important source to potential HGT exchanges.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, we calculated the removal of each target gene across the treatment processes during the 24 h sampling period based on gene loads, which accounted for the plant flow rate (Figure ). The load of ARGs in the treated effluent may be more informative as compared to the concentrations of ARGs to indicate ARG dissemination into effluent-receiving environments because it represents the actual abundance of ARGs released from a WWTP over a specified period of time. We found that all target genes were reduced in terms of 24 h loads (Figure a,b), but the degree of removal varied for different targets and across different unit processes (Figure c,d).…”
Section: Resultsmentioning
confidence: 92%
“…For the ARGs, we noticed that tet-associated iARGs in the effluent increased and were affected by membrane pore size. This accentuates the conclusion drawn by Wang et al (2019) on the ramification of antibiotic exposure on the abundance of intracellular ARGs. The UF membrane demonstrated superior restraint of tet-asociated iARGs into the effluent in comparison to the MF1 membrane.…”
Section: Tetracycline Args In Effluents Before Vs After Tetracycline ...mentioning
confidence: 56%